IDENTIFIKASI MISKONSEPSI DALAM MATERI SISTEM PERNAPASAN PADA SISWA SMP - Aisya Muawana; Erman Erman (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research aimed to identify students' misconceptions about Respiratory System. This research was survey research involving 64 students of class VIII from two classes at Junior High School 5 Gresik who has just finished studying the Human Respiratory System. Data collection techniques through a test results, interviews, and document analysis includes analysis of science textbooks and student notebooks. The results showed that there were students' misconceptions about the Human Respiratory System consisted of the concepts of respiratory volume, respiratory mechanism, respiratory disorders, respiratory frequency, and respiratory organs. The research concluded that there were misconceptions in the Human Respiratory System with a low category. This was evidenced by the characteristics of various misconceptions with diverse characteristics so that it can be known that the cause of students' misconceptions themselves were the result of incomplete or incorrect reasoning.